2003
DOI: 10.1084/jem.20021787
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Induction of Inflammatory Responses by Dectin-1 and Toll-like Receptor 2

Abstract: Toll-like receptors (TLRs) mediate recognition of a wide range of microbial products including lipopolysaccharides, lipoproteins, flagellin, and bacterial DNA, and signaling through TLRs leads to the production of inflammatory mediators. In addition to TLRs, many other surface receptors have been proposed to participate in innate immunity and microbial recognition, and signaling through some of these receptors is likely to cooperate with TLR signaling in defining inflammatory responses. In this report we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

62
1,319
6
32

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,483 publications
(1,419 citation statements)
references
References 50 publications
62
1,319
6
32
Order By: Relevance
“…These results agree with the reports that in murine macrophages dectin-1 plays a role in ROS production [27,39], and with previous findings demonstrating an inhibitory effect of CD206 on proinflammatory cytokine release [40,44,47]. Moreover, these results may explain why Candida does not elicit the NADPH oxidase activity in DC.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results agree with the reports that in murine macrophages dectin-1 plays a role in ROS production [27,39], and with previous findings demonstrating an inhibitory effect of CD206 on proinflammatory cytokine release [40,44,47]. Moreover, these results may explain why Candida does not elicit the NADPH oxidase activity in DC.…”
Section: Discussionsupporting
confidence: 93%
“…4C), confirming early studies [39,42]. Consistently with reports showing that dectin-1 induces ROS production in murine macrophages [27,39], this finding suggests that dectin-1 could mediate NADPH oxidase activation in human DC. …”
supporting
confidence: 90%
See 1 more Smart Citation
“…In the case of gram-positive bacterial components, evidence suggests that CD14 can enhance TLR2-dependent signaling in macrophages (Harokopakis and Hajishengallis, 2005;Manukyan et al, 2005;Schroder et al, 2003). The majority of Toll-like receptors identified to date utilize a common signal transduction pathway with minor differences that appear to confer specificity in response to distinct ligands (Akira and Hemmi, 2003;Gantner et al, 2003;Takeda et al, 2003). MyD88 is a central player in the signal transduction pathways of the IL-1R, IL-18R, and TLRs (with the exception of TLR3), providing a bridge between the cytoplasmic domains of these receptors and IL-1R-associated kinase (IRAK) (Akira and Hemmi, 2003;Kawai and Akira, 2005;Takeda et al, 2003;Yamamoto et al, 2004).…”
Section: Modulation Of Cd14 Ko Microglial Activation In Response To Bmentioning
confidence: 99%
“…It was reported that TLR2 together with Dectin-1 is capable of sensing zymosan in murine bone marrow-derived DC and that hyphae of Candida albicans prime monocyte-mediated Th17 responses [24,25]. In case of injury and breakdown of the skin barrier or otherwise microbial invasion, LC gain access to TLR-agonist-bearing pathogens.…”
Section: Introductionmentioning
confidence: 99%